Facility manager's operation and maintenance handbook - Lewis, Bernard T. (McGraw-Hill handbooks, 1999)
Let 21 top specialists show you how to maximize the operation and maintenance capabilities of any facility or plant. This practical handbook takes you through each step in the planning, design, and execution of maintenance and operation procedures for structures, equipment, and systems. It features special emphasis on emergency and energy equipment used in facilities--and explores all essential support functions and duties. The most comprehensive resource of its kind, this handbook provides you with a complete picture of facility operation and maintenance--from technical checklists--to cost control--to computer applications!